EFEKTIVITAS PENATAAN KOLEKSI BERDASARKAN BIDANG ILMU TERHADAP KEMUDAHAN AKSES INFORMASI DI PERPUSTAKAAN PASCASARJANA UNIVERSITAS NEGERI PADANG - Indah mulya kurniawan; Marlini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to assess the effectiveness of subject-based collection organization in facilitating information access at the Postgraduate Library of Universitas Negeri Padang. The Dewey Decimal Classification (DDC) system has been applied to all collections; however, the physical arrangement of shelves is organized according to academic disciplines such as Educational Technology, Educational Administration, Social Sciences, Mathematics and Natural Sciences, Indonesian Language, English Language, Physical Education, and Environmental Science. This research employs a qualitative method through a literature review of relevant national and international sources. The analysis reveals that subject-based shelving enhances the efficiency of locating materials, increases user satisfaction, and improves information retrieval. The integration between the DDC catalog and the physical shelf arrangement is a crucial factor in maintaining system effectiveness. The main challenges involve maintaining catalog metadata consistency and managing interdisciplinary collections, which require specific labeling strategies. Overall, this system is considered efficient and well-suited to the needs of postgraduate users who focus on thematic research. The study provides recommendations for academic libraries to develop a collection organization model that balances bibliographic standardization with physical accessibility for users.